Mobile marketing in promotion practice of products of Russian (Путеводитель предпринимателя)
The article devoted to the problems of mobile marketing, considers the main possibilities of use of mobile devices potential in marketing practice of the entities. The application of modern marketing methods allows the entities to concentrate efforts on target groups of consumers, thereby to spend effectively the marketing promotional budget.